PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS V MELALUI PEMBELAJARAN BERBASIS MATEMATIKA REALISTIK BERBANTUAN POWTOON - Lisa Virdinarti Putra; Yohannes Romando Sipayung (Jurnal Guru Kita PGSD, 2019)
Abstract: Enhancement Of Class V Study Problem Solving Skills Through Powtoon Based Realistic Mathematics Learning. This study aims to improve the problem solving ability of fifth grade students using powtoon-assisted media as a learning aid for students in learning realistic mathematical solving. Data analysis techniques used in this study consisted of two, namely: descriptive analysis and inferential analysis. Descriptive analysis is used to analyze teacher activity data, student activities during learning, test results of problem solving abilities before and after the use of powtoon-assisted realistic mathematics learning. The average problem solving ability of the experimental class students is higher than the problem solving ability of the control class students. It can be said that the problem-solving abilities of the experimental class students increased compared to before being given treatment.Keywords: Problem solving skill, realistic mathematics learning, powtoonAbstrak: Peningkatan Kemampuan Pemecahan Masalah Siswa Kelas V Melalui Pembelajaran Berbasis Matematika Realistik Berbantuan Powtoon. Penelitian ini bertujuan untuk meningkatkan kemampuan pemecahan masala siswa kelas V menggunakan media berbantuan powtoon sebagai alat bantu belajar siswa dalam pembelajaran pemecahan matematika realistik. Teknik analisis data yang digunakan dalam penelitian ini terdiri atas dua, yaitu: analisis deskriptif dan analisis inferensial. Analisis deskriptif digunakan untuk menganalisis data aktivitas guru, aktivitas siswa selama pembelajaran, hasil tes kemampuan pemecahan masalah sebelum dan setelah penggunaan pembelajaran matematika realistik berbantuan powtoon. Rata-rata kemampuan pemecahan masalah siswa kelas ekperimen lebih tinggi dari pada kemampuan pemecahan masalah siswa kelas kontrol. Dapat dikatakan bahwa kemampuan pemecahan masalah siswa kelas eksperimen meningkat dibandingkan sebelum diberikan perlakuan.Kata Kunci: kemampuan pemecahan masalah; pembelajaran matematika realistik; powtoon